(untitled) (Communications in Mathematical Research, 2021)
In this paper, we discuss the anti-periodic boundary value problem for a class of first order differential equations. By using homotopy method, we obtain the conditions for the existence of anti-periodic solution for the equation under consideration. This result can be extended to higher order differential equations.